Maya 6 Revealed - Murdock, Kelly L. (Thomson Course Technology, 2011)
"Maya 6 Revealed" shows readers how to use this popular 3D modeling, animation and rendering package. 3D graphics such as those created using Maya have appeared in movies, television and games and as the demand for these types of images increase, so will the number of 3D artists wishing to learn these skills. A book focused on beginners that offers quality content in a smooth and relaxed style will appeal to this broad audience and enable them to gain the skills they desire. This book's approach is to present quality content with a modest price point written by an experienced professional.